Increased correlation between methylation sites in epigenome-wide replication studies: impact on analysis and results. (December 2017) - Popovic, Maja; Fasanelli, Francesca; Fiano, Valentina; Biggeri, Annibale; Richiardi, Lorenzo
Aim: To show that an increased correlation between CpGs after selection through an epigenome-wide association studies (EWAS) might translate into biased replication results.Methods: Pairwise correlation coefficients between CpGs selected in two published EWAS, the top hits replication, Bonferroni p-values, Benjamini–Hochberg (BH) false discovery rate (FDR) and directional FDR r-values were calculated in the NINFEA cohort data. Exposures' random permutations were performed to show the empirical p-value distributions.Results: The average pairwise correlation coefficients between CpGs were enhanced after selection for the replication (e.g., from 0.12 at genome-wide level to 0.26 among the selected CpGs), affecting the empirical p-value distributions and the usual multiple testing control.Conclusion: Bonferroni and Benjamini–Hochberg FDR are inappropriate for the EWAS replication phase, and methods that account for the underlying correlation need to be used.